Differential detection of Entamoeba histolytica, Entamoeba dispar and Entamoeba moshkovskii in faecal samples using nested multiplex PCR in west of Iran. (2019) - Bahrami, Fares; Haghighi, Ali; Zamini, Ghasem; Khademerfan, Mohammadbagher
Abstract: This study aimed to determine the prevalence of Entamoeba histolytica, Entamoeba dispar and Entamoeba moshkovskii (collectively referred to as Entamoeba complex), using microscopic and molecular methods in Kurdistan Province, northwest of Iran. The relationship between positive Entamoeba species and clinical symptoms was also investigated. Eight positive Entamoeba complex, as well as four Entamoeba complex-like isolates, were detected by microscopic stool examination. DNA was extracted from all positive and from 55 randomly selected negative stool samples. PCR was performed using species-specific 18S rRNA primers for the Entamoeba complex. All positive PCR samples were sequenced. In total, 14 (1.01%) out of 1383 isolates, i.e. 12 microscopy-positive and Entamoeba complex-like isolates and two out of 55 microscopy-negative isolates, were identified via PCR and sequencing. Overall, 0.58% (8/1383) of the isolates were E . dispar, 0.14% (2/1383) E . histolytica, 0.07% (1/1383) E . moshkovskii and 0.22% (3/1383) were mixed of E . histolytica and E . dispar . Based on our findings, the prevalence of E. dispar is greater than that of E. histoltyica . On the other hand, a case of E. moshkovskii was reported for the first time in this region. It seems that some gastrointestinal symptoms may be attributed to Entamoeba species.